Beauty - Ratcliff, Carter 1941-; Earnest, Jarrett ca. 20. Jh (Karma Books, 2021)
This handsome clothbound catalog gathers Alex Katz's recent titular print portfolio. The series of 25 prints features close-up, black-and-white portraits that remove the subjects from any contextual backdrop, emphasizing instead subtle shifts in expression. Rendered in bold lineation and tightly framed, the women depicted recall the models and celebrities featured in mid-20th-century fashion imagery, underscoring Katz's ongoing fascination with perceptions of beauty and glamour that permeate the public sphere. The portraits are bookended by a pair of meditations on beauty: Carter Ratcliff imagines a comedically philosophical dialogue between himself and beauty, and Jarrett Earnest shares 31 encounters with beauty in art and life. Alex Katz (born 1927) is one of America's most iconic and prolific artists. His work has been the subject of more than 250 solo exhibitions and 500 group exhibitions since 1951 and can be found in over 100 public collections worldwide. Katz is best known for his large-scale canvases of flatly rendered figures cast against a monochrome background
Edition of 2000
Keywords: Katz, Alex -- 1927-; Katz, Alex / 1927-; Prints, American / 20th century; Pop art / United States; Pop art; Prints, American; United States; 1900-1999; Bildband